Actualizing Malay communication ethics in social media: Study of the Kitab Kumpulan Ringkas Berbetulan Lekas - Mawazi, Abd Rahman; Yonantha, Ferri (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
This research stems from the rampant negative impact of social media as a medium of communication in the cyber era, such as crime, cyber violence, sexual harassment, pornographic content, gossipy infotainment, and so on. This study uses the content analysis method that is extracted from the parts of values of communication ethics in Kitab Kumpulan Ringkas Berbetulan Lekas (KRBL) written by Raja Ali Kelana. The urgency of this research is part of the effort to answer the needs of today based on past experiences and as part of maintaining the value of wisdom that lives in the treasury of knowledge in Malay. The results of the study of the content of communication ethics in KRBL show that the principles of communication ethics contained therein are speaking the truth, being knowledgeable, not indulging in disgrace, speaking softly, not arguing, and maintaining confidentiality. These values seem to be very normative and in line with the values in Islamic teachings and universal values in communication. The content of communication ethics values in KRBL is also still quite relevant to be actualized in social media. From this study, it is also revealed that the intellectual legacy of Nusantara figures enriches the study of Islamic communication, necessitating further research on different figures, approaches, and subjects. ***** Penelitian ini dilatarbelakangi oleh maraknya dampak negatif media sosial sebagai media komunikasi di era siber, seperti kriminalitas, kekerasan siber, pelecehan seksual, konten pornografi, infotainment yang bersifat gosip dan lain sebagainya. Penelitian ini menggunakan metode analisis isi yang digali dari nilai-nilai etika komunikasi dalam Kitab Kumpulan Ringkas Berbetulan Lekas (KRBL) yang ditulis oleh Raja Ali Kelana. Urgensi penelitian ini adalah sebagai bagian dari upaya menjawab kebutuhan masa kini berdasarkan pengalaman masa lalu dan sebagai bagian dari mempertahankan nilai kearifan yang hidup dalam khazanah ilmu pengetahuan dalam bahasa Melayu. Hasil kajian terhadap muatan etika komunikasi dalam KRBL menunjukkan bahwa prinsip-prinsip etika komunikasi yang terkandung di dalamnya adalah seperti berkata benar, berilmu, tidak mengumbar aib, bertutur kata lemah lembut, tidak berbantah-bantahan, dan menjaga kerahasiaan. Nilai-nilai tersebut terlihat sangat normatif dan sejalan dengan nilai-nilai dalam ajaran Islam dan nilai-nilai universal dalam berkomunikasi. Muatan nilai-nilai etika komunikasi dalam KRBL juga masih cukup relevan untuk diaktualisasikan dalam media sosial. Dari penelitian ini, diketahui juga bahwa khazanah pemikiran tokoh Nusantara memperkaya kajian komunikasi Islam sehingga perlu diteliti lebih lanjutan, baik terhadap tokoh, pendekatan, maupun obyek yang berbeda.